Relationships between emotional intelligence, parent-child relationship, deviant peer affiliation, and aggressive behavior among adolescents in Tehran, Iran - Homauni, Masoumeh (2014)
Aggression has considerably increased among adolescents in Iran. Recently, there has been growing attention on the effects of aggression on adolescents and their wellbeing. Even though the relationships between emotional intelligence, parent-child relationship and deviant peer affiliation with adolescents’ aggression have been established, however, it has received little attention in Iran. To address this paucity, the present study was conducted to examine the relationship between emotional intelligence, parent-child relationship, deviant peer affiliation and adolescents’ aggression. Additionally, this study examined the moderating role of parent–child relationships on the relationship between emotional intelligence and deviant peer affiliation with adolescent’s aggression. Thus, the present study is essential and necessary. This study is a quantitative study and utilized a correlation design. 400 adolescents between 16 -18 years old from 20 government high schools in five selected districts in Tehran, Iran were selected as respondents for this study. Multi-stage cluster sampling technique was employed to obtain the research sample. Data werecollected using a self-administered questionnaire. The questionnaires consisted of Emotional Intelligence Scale (Bar-one’s EI), Aggression Questionnaire (Bus and Perry), Deviant Peer Affiliation Questionnaire andQuality ofParent-Child Relationships Questionnaire(PCRS).All the instruments used in this study were highly reliable. Descriptive, bivariate and multivariate statistics were used in data analysis. The results of the Pearson correlation analyses indicated that emotional intelligence; parent-child relationship and deviant peer affiliation were significantly related to adolescents’ aggression. The result of t-test showed that there is no significant difference in total aggression between male and female adolescents. The hierarchical regression analyses revealed that emotional intelligence, parent-child relationship and deviant peer affiliation were significant predictors of aggression among adolescents. Emotional intelligence emerged as the strongest predictor of aggression among adolescents in Tehran, Iran. The results of this study highlighted the important role of emotional intelligence, the quality of parent-child relationship and deviant peer affiliation to prevent aggression among adolescents in Tehran, Iran. The findings also unveiled that parent-child relationship moderate the relationship between emotional intelligence, deviant peer affiliation and adolescents’ aggression. When parents-child relationship was at high level (positive), there was a weak negative relationship between emotional intelligence and aggression. It means, as emotional intelligence decreased, adolescents with moderate to high levels of parents-child relationship report lower level of aggression than those with a low level of parentschild relationship. Findings of this study also revealed that when parents-child relationship was at high level, there was a weak positive relationship between deviant peer affiliation and aggression, and when parents-child relationship was at low level, there was a strong positive relationship between deviant peer affiliation and aggression. As deviant peer affiliation increased, adolescents with moderate to high levels of parents-child relationship reported a lower level of aggression than those with low level of parentschild relationship. This study revealed that the quality of parent-child relationship have beneficial effects on adolescents’ behavior. This study also suggested that parent-child relationship is important to consider in planning, implementation and evaluating programs for adolescents. The present study has significant recommendation for future research and practices. Since this study was conducted among adolescents in Tehran, Iran, therefore to generalize the result of the study to other population it is recommended similar study can be conducted in other regions of the country and with different age group and demographic characteristics.